Development of Low-Cost CNC-Milled PMMA Microfluidic Chips as a Prototype for Organ-on-a-Chip and Neurospheroid Applications - Sushmita Mishra; Ginia Mondal; Murali Kumarasamy (Organoids)
Improved in vitro models are needed to reduce costs and delays in central nervous system (CNS) drug discovery. The FDA Modernization Acts 2.0 and 3.0 require human-centered alternative testing methods to mitigate animal-based experiments and discovery delays, and to ensure human safety. Developing cost-efficient, flexible microfluidic chips is essential to advance organ-on-chip (OoC) technology for drug discovery and disease modeling. While CNC micromilling shows promise for fabricating microfluidic devices, it remains underutilized due to limited accessibility. We present a simple CNC-milled flexible microfluidic chip fabricated from thermoplastic poly (methyl methacrylate) (PMMA). The structure of the microplate included drilled openings for connecting the wells. The chip’s biocompatibility was evaluated with isolated primary neuronal cultures from postnatal Wistar rat pups (p1). Primary cells cultured in the device showed high viability, differentiation, and 3D neurosphere formation, similar to conventional well-plate cultures. Neuronal cultures showed neurite growth and functional markers. Although cleanroom-based methods provide higher accuracy, the chip effectively promotes cell viability, differentiation, and alignment, offering an ideal platform for tissue modeling and OoC applications. It allows cell biologists to quickly create prototypes at lower cost and in less time than required for soft lithography and is a viable alternative to the current manufacturing methods.